REFLECTIONS ON CANCER REHABILITATION AND SURVIVORSHIP IN CANADA: OBSERVING TEN YEARS OF EVIDENCE INFORMED PRACTICE - Arminee Kazanjian; Jennifer M. Jones; Linda E. Carlson; Martin Chasen; Ravi Bhargava; David Langelier (Journal of Cancer Rehabilitation, 2019)
Given the relative novelty of cancer survivorship in Canada, much seminal work in the area has revolved around establishing basic characteristics and program implementation groundwork. Despite commendable efforts and investments, more work is needed to understand needs and characteristics of unique or vulnerable populations. In the early 2000s, a flurry of initiatives to formally establish survivorship practice and research in Canada was undertaken. A groups of clinicians, clinician scientists, survivorship researchers, and survivors collaborating on the development of practice guidelines on survivorship services for adult populations. These were developed under the stewardship of the Cancer Journey Advisory Group of the Canadian Partnership Against Cancer (CPAC) and the Canadian Association of Psychosocial Oncology (CAPO). As the focus of cancer rehabilitation aligns closely with the principles of survivorship care, this suggests the need to more formally integrate rehabilitation specialists in standard survivorship care. Once early national initiatives were underway, cancer control organizations and cancer researchers across the country began to develop strategic policies in an effort to improve and standardize care. There have been some innovative and unique regional programs developed such as physical activity prescriptions, routine screening for distress and rehab for palliative care, which we discuss. Such initiatives were developed in an effort to improve cancer survivorship services and support for survivors anywhere in Canada. Person-centered care is a central element in this body of work, supported by research funding bodies such as the Canadian Institutes of Health Research (CIHR) and the Canadian Cancer Society (CCS). The shifts in patient care in the last decade are influenced by broader changes in understanding health and illness. The dominant model of disease has shifted from a pathological model to a clinical focus on risk factors and medical surveillance. Increasing focus on terms such as ‘risk’, ‘behavior’ and ‘lifestyle’ have come to take on new meanings in survivor care, influenced by disciplines examining human behavior such as psychology and sociology. In the next decade, new ventures in international collaboration would increase knowledge translation of research findings and achieve evidence guided practice across the continents.